Case Report: Paralytic ileus as an early manifestation of evolving neuroleptic malignant syndrome in a patient receiving anti-psychotics - Balakrishnan Arivalagan; Pragathi Munnangi; Yashkumar Girdharlal Kamani; Jyoti Guglani; Angel Barrera; Krishna Singh; Makker Jasbir; Harish Patel; Misbahuddin Khaja (Frontiers in Medicine, 2026)
Neuroleptic malignant syndrome (NMS) is an uncommon, but potentially life- threatening complication of antipsychotic therapy, primarily resulting from central dopaminergic blockade. NMS is a clinical diagnosis and occurs rarely in patients receiving atypical antipsychotics agents. Gastrointestinal manifestations, including severe hypomotility and paralytic ileus, are recognized adverse effects of antipsychotic medications. However, paralytic ileus preceding the characteristic neuromuscular and autonomic features of NMS is exceptionally rare and underrecognized as an early manifestation of the syndrome. We report the case of a 49-year-old man who presented with progressive abdominal distension secondary to intestinal pseudo-obstruction as an early manifestation of NMS. This atypical and underreported presentation highlights the importance of maintaining a high index of suspicion for NMS in patients receiving antipsychotic therapy who develop unexplained gastrointestinal dysmotility. Prompt recognition, immediate discontinuation of the offending antipsychotic agent, and early initiation of treatment with dantrolene and bromocriptine resulted in a favorable clinical outcome.